Primeiros seis anos: uma narrativa crítico-reflexiva - Pereira, Beatriz Caroline dos Santos (Universidade Federal de São Carlos, 2024)
This Final Graduation Project (TCC) was developed based on the guidelines of the Political-Pedagogical Project (PPP) of the UFSCar Medical School, adopting a critical and reflective approach from the personal perspective of a student. The text narrates, in chronological order, the academic journey throughout six years of medical education, structured into three formative cycles of two years each. The first cycle was marked by insecurity, challenges related to the teaching methodology, and difficulties in integrating with peers, further intensified by the uncertainties of the pandemic. During the second cycle, there was a phase of readjustment to the post-pandemic context, marked by struggles with learning and mental health. In the third cycle, the practical nature of the internship and interaction with a group of peers led to significant improvements in the learning process and personal development. This narrative reflects on the technical and human evolution throughout the course, culminating in a broader, critical, and empathetic view of medical practice.
First six years: a critical-reflective narrative
Keywords: Metodologia ativa; Medicina; Narrativa crítico-reflexiva; Active methodology; Medicine; Critical reflective narrative; CIENCIAS DA SAUDE::MEDICINA